Three-dimensional morphological and biomechanical analysis of temporomandibular joint in mandibular and bi-maxillary osteotomies. Issue 12 (30th August 2022) - Shao, Bingmei; Li, Annan; Shu, Jingheng; Ma, Hedi; Dong, Shiming; Liu, Zhan
Abstract: Orthognathic surgery is a typical approach for treating maxillofacial deformities. However, orthognathic surgery results in positional changes in the condyles. In a previous review, the effects of orthognathic surgery on temporomandibular joints (TMJs) are not provided. Hence, in this study, we investigate the morphological changes in TMJs after mandibular and bi-maxillary osteotomies. The relationship between the morphological parameters of TMJs and symptoms of temporomandibular disorders (TMDs) is discussed. Finite element contact stress analysis is performed, and the results show that the two abovementioned surgeries can improve maxillofacial deformities, although the positions of the condyles are changed. Moreover, preoperative stress asymmetry of the left and right TMJs is observed, which remain after the surgeries. TMD patient-specific analysis shows that three joint spaces (medial joint space, lateral joint space, superior joint space) are significantly correlated with TMD symptoms.